CLINICAL AND LABORATORY PARAMETERS AS PROGNOSTIC AND MONITORING BIOMARKERS IN PATIENTS WITH CARDIOVASCULAR AND METABOLIC DISEASES - Wille, Daniele Fernanda; da Silva, Fernanda D’Avila; Quines, Caroline Brandão; Frizzo, Matias Nunes (Seven Editora, 2026)
Non-communicable chronic diseases represent one of the greatest contemporary challenges to public health due to their high prevalence, impact on morbidity and mortality, and the need for continuous care. In this context, systemic arterial hypertension and type 2 diabetes mellitus play a central role, both because of their frequency in the population and the complexity of their cardiovascular, renal, and metabolic complications. This chapter highlights the importance of using clinical and laboratory biomarkers as tools to support risk stratification, prognosis, and monitoring of these conditions, especially in Primary Health Care. Among the clinical parameters, anthropometric measurements, blood pressure, and cardiovascular assessment stand out, while, in the laboratory field, blood glucose, glycated hemoglobin, lipid profile, renal and hepatic markers, as well as hematological and inflammatory indices derived from complete blood count analyses, gain relevance. The integration of these different parameters makes it possible to increase the sensitivity of clinical assessment, promote the early identification of subclinical alterations, and support individualized management strategies. Thus, the combined use of clinical and laboratory biomarkers constitutes a promising strategy to improve health care quality, especially in resource-limited settings, contributing to the prevention of complications and to better outcomes in patients with chronic diseases.